Concomitant ruptured anterior circulation and unruptured posterior circulation aneurysms: Treatment strategy and review of literature. (August 2019) - Janjua, M. Burhan; Reddy, Sumanth; Welch, William C.; Ozturk, Ali K.; Price, Angela V.; Weprin, Bradley; Swift, Dale M.; Krisht, Ali F.
Highlights: Concomitant blister-type anterior & basilar apex aneurysm. Aberrant basilar apex thalamoperforators. Treatment rationale of ruptured & unruptured aneurysms. Abstract: Basilar artery apex or bifurcation is the most common location for aneurysms arising from posterior cerebral circulation. Reports of unruptured aneurysms of the basilar bifurcation associated with ruptured anterior circulation aneurysms are rare. The presence of multiple intracranial aneurysms poses a significantly high risk to management than a single aneurysm due several factors involved. Surgical management is considered the best treatment modality for most aneurysmal types and location with quite a few limitations when applicable. Authors have conducted a literature review of anterior and posterior circulation concomitant aneurysms and report their own experience with a case of anterior communicating artery blister type aneurysmal rupture presented with the symptoms and signs of subarachnoid hemorrhage concomitant with an unruptured basilar artery bifurcation aneurysm. Moreover, the anomalous origin of thalamoperforators at the basilar apex instead of the posterior cerebral artery makes it reasonably challenging for the microsurgical clipping. Discussed is the clinical presentation, radiological studies obtained, surgical approach utilized with an adequate exposure of the entire circle of Willis as well as the critical decision making when managing these challenging cases.